How Is AI-created Music Being Commercialized Outside Of The Recording Industry? - Tomás de Andrade Ramos Pinheiro (2021)
Artificial intelligence (AI) to create music is still in its early days as a technology, and the music industry has been in a state of constant transformation for the past twenty years. Almost nothing is known about the practical use of artificial intelligence by the recording industry to create, record and sell new music. Most of the literature about the combination of AI and the music industry is focused on the technological advances, applications and challenges of creating music with AI. However, researchers have not paid much attention to this innovation's business elements or how the music industry can best embrace this technology. This dissertation focuses on mapping the companies that are using AI-created music worldwide and synthesising their technologies, products, services and business models. Secondary data collected from websites of the companies were used as a reference to understand how those elements interact. Moreover, a taxonomy of categories was created to group similar solutions and better visualise and comprehend the different businesses model. The results of this work display current references about the most common business models using AI-created music, its different applications and the number of companies operating in the market. Recording and music industry executives, innovation managers and business researchers will be able to use the contents of this research as a reference to explore, understand and innovate with AI-created music in their industry.